(untitled) (Revista Lusófona de Educação, 2025)
Education is an unresolved issue, there is a disconnect between the citizen who is seen in the future and what is learned in the classroom. Real spaces for participation must be offered that imply the construction of a more equitable society, where human rights are respected and equality of opportunity is promoted within the framework of Critical Theory and social justice. The objectives are aimed at knowing and understanding the forms of transformative resistance in resilient schools from the macro project called Transformative Resistance in Schools, Counternarratives in Education for Social Justice (EscuelaQResiste) and deepening the knowledge of critical consciousness in these schools. The methodological treatment for understanding the actions of transformative resistance in schools is ethnographic. The techniques used were participant observation, the critical testimony and documentary analysis. The main conclusions of the case presented revolve around the school’s educational model, which allows communities to promote autonomy in defining their own educational models and encourage the active participation of students and the community, promoting critical thinking about the State and public policies from a human rights perspective. Keywords: Citizenship; Social justice; Endurance.